2016
DOI: 10.1007/s40866-016-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Parameters on Augmentation of Distillate Output of Solar Still: A Review

Abstract: A Simple device which is used to obtain fresh water from saline water with the use of solar desalination process is known as solar still. The simple solar still give an output of 2.5 to 5 litres per 1m 2 area per day during bright sunshine hours. Hence various investigation has been done by scientists and researcher to improve the performance of solar still by inspecting various design parameters(water depth, condensing cover material, its thickness and inclination, type of solar still), climatic parameters(wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Panchal and Patel [11] carried out a comprehensive review to study the effect of various design parameters (water depth, condensing cover material, thickness and inclination, and type of solar still), climatic parameters (wind velocity, ambient temperature, and solar radiation), and operational parameters (salinity of water) on the distillate yield of solar stills. It is found that the lower condensing glass cover thickness, minimum brine depth, high intensity of solar radiation, and increasing wind speed give the better yield of the solar stills.…”
Section: Gawande and Bhuyarmentioning
confidence: 99%
“…Panchal and Patel [11] carried out a comprehensive review to study the effect of various design parameters (water depth, condensing cover material, thickness and inclination, and type of solar still), climatic parameters (wind velocity, ambient temperature, and solar radiation), and operational parameters (salinity of water) on the distillate yield of solar stills. It is found that the lower condensing glass cover thickness, minimum brine depth, high intensity of solar radiation, and increasing wind speed give the better yield of the solar stills.…”
Section: Gawande and Bhuyarmentioning
confidence: 99%
“…The potable water scarcity problem worsens day by day due to various applications such as drinking, industrial applications and many more [1]. In many areas of the world, people suffer from many diseases due to the scarcity of potable water [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sebaii and Nagar [45] found that the fins' material did not affect the distillate productivity of the solar still. The productivity of a solar still could also be increased by various parameters reviewed by Panchal and Patel [1]. Diesel engine exhaust gases used with a solar desalination system were evaluated by Panchal Hitesh [38] to enhance distillate productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Solar thermal technology is the traditional method to conserve the continuous use of fossil fuel to evaporate water. Multistage flash, membrane desalination, and reverse osmosis technique were developed with the constant operation for mass production of drinking water, whereas it consumes electrical energy as the primary source and requires higher land capacity with initial investment . Even the quality of produced fresh water in direct incorporation of particles in the fluid is questionable.…”
Section: Introductionmentioning
confidence: 99%